Methodology and Results of Studying the Electrophysical Properties of Plants (Texas Journal of Engineering and Technology, 2025)
This article discusses methods for studying the electrophysical properties of plants, the importance of bioelectric parameters in determining their physiological state, and experimental results. As a result of the research, it was proven that changes in the capacitance and resistance of plant cell membranes are an important indicator in determining their response to external factors.